Implementasi Model Pembelajaran Kasus Unsung Cinderella pada Farmakoterapi untuk Menguatkan Kesadaran Peran Farmasi di Masyarakat - Yuliawati Yuliawati; Fathnur Sani K; Elisma Elisma; Marizki Pondawinata (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
The role of pharmacy in healthcare services requires cognitive and affective skills, as well as strong communication abilities. However, in Indonesia, pharmacists’ involvement in direct patient care remains limited; therefore, innovative learning models are needed to foster awareness of the pharmacist’s role in society. This study aimed to implement a case-based learning model utilizing the Unsung Cinderella drama series in the Pharmacotherapy II course. The research was conducted among students of the Pharmacy Study Program, University of Jambi, during the odd semester of the 2023/2024 academic year. The method used was classroom action research, involving stages of case study implementation, group discussions, presentations, role-playing, and evaluations through questionnaires and activity documentation. The results showed that the implementation of the case-based learning model using the Unsung Cinderella series achieved an average student satisfaction rate of 80.4%, categorized as very good, and enhanced students’ understanding of the pharmacist’s role according to the Ten Star Pharmacist framework.